The Potential of Straw for Energy Purposes in Poland - Piotr Gradziuk (Barometr Regionalny, 2014)
The paper presents the results of studies aimed at determining the potential of the use of straw for energy in Poland. The results of this analysis have been presented in a dynamic approach for the years 1975–2011, and in a territorial (by voivodship) approach for the years 1999–2011. These studies demonstrate that since 1983 straw harvests have exceeded the requirements of agricultural production. During the years 1983–1990, the average surplus over agricultural consumption amounted to 4 971 thousand tons, and recently, during the years 2007–2011, already 15 190 thousand tons. The quantity of these surpluses varies greatly by region, as it depends on the structure of land tillage, crop structure, farm size, as well as the type of livestock and the manner of husbandry. The greatest potential for using straw for energy-related purposes was noted in the following voivodships: Wielkopolskie, Lubelskie, Zachodniopomorskie, and Kujawsko-Pomorskie.